Effectiveness of allergen-specific immunotherapy in children with bronchial asthma sensitized to house dust mites - M.P. Prokhorova; O.P. Volosovets; S.P. Kryvopustov; A.V. Kupkina; T.M. Volosovets (Zaslavsky O.Yu., 2024)
Background. The only method of treatment that can change the natural course of allergies is allergen-specific immunotherapy, which allows reducing the sensitivity of the child's body to the causative allergen and decreasing the activity of chronic inflammation. The evidence base for the effectiveness of allergen-specific immunotherapy in the treatment of bronchial asthma (BA) has significantly expanded recently. However, the truly important results remain too limited to make clinically useful conclusions about the efficacy of sublingual allergen-specific immunotherapy (SLIT) in people with BA and further evidence is needed. The purpose of the study is to evaluate the effectiveness of SLIT as an additional treatment for atopic BA of varying severity in children sensitized to house dust mites. Materials and methods. The main group consisted of 80 children with BA aged from 5 to 17 years, they were divided into three groups according to the severity of the disease: group 1 - 20 children with mild intermittent asthma, group 2 - 30 children with mild persistent asthma, group 3 - 30 children with moderately severe persistent asthma. Thirty practically healthy children without BA were also examined as a control group. For SLIT, a sublingual ORALTEK spray produced by Inmunotek (Spain) was used, a mixture of house dust mite allergens Dermatophagoides pteronyssinus 50 %/Dermatophagoides farinae 50 %, 1 ml of the solution contains 30,000 IU of natural allergen extract. To assess the effectiveness of the treatment, we conducted an analysis of the total score of clinical manifestations of asthma and allergic rhinitis and the degree of asthma control according to the Asthma Control Test. We also analyzed the state of cellular and humoral immunity in the dynamics of therapy. These indicators were evaluated within 1 month before the beginning and a month after the end of the one-year course of therapy. To assess the validity and reliability of the obtained results, statistical data processing was carried out using Microsoft Excel 2016 and Statistica for Windows 10 programs. The Student's t-test was applied to assess the reliability of the results. The difference between the compared values was considered statistically significant at p < 0.05. Results. The results of the statistical analysis confirmed a significant improvement in the control indicators of patients who received SLIT: reduction in the total score of clinical manifestations, the frequency of clinical symptoms and the use of emergency drugs (p < 0.05). By the end of the study, the dynamics of a decrease in these indicators compared to the data before the start of treatment (according to the above list) was as follows: in patients of group 1 - 82.5, 91.8, 94.5 %, in patients of group 2 - 80.5, 88.4, 92.7 %, in patients of group 3 - 76.7, 85.3, 91.2 %. After treatment with the addition of SLIT to the basic therapy, a reliable increase in IgE and sIgA was observed, an increase in the spontaneous proliferative response of T-lymphocytes to the mitogen in all three groups to the level of the controls, a probable decrease in eosinophilic inflammation and an improvement in indicators of the cellular and humoral immunity (p < 0.001). Conclusions. The prescription of SLIT to children with mild intermittent BA, mild persistent BA and perennial allergic rhinitis, moderate persistent BA and perennial allergic rhinitis provides an opportunity to obtain stable control of the disease, reduces the number of visits to the doctor and justifies the wide use of this method in clinical allergy practice.